If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -3 = 4x + 2 Reorder the terms: -3 + -1x = 4x + 2 Reorder the terms: -3 + -1x = 2 + 4x Solving -3 + -1x = 2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -3 + -1x + -4x = 2 + 4x + -4x Combine like terms: -1x + -4x = -5x -3 + -5x = 2 + 4x + -4x Combine like terms: 4x + -4x = 0 -3 + -5x = 2 + 0 -3 + -5x = 2 Add '3' to each side of the equation. -3 + 3 + -5x = 2 + 3 Combine like terms: -3 + 3 = 0 0 + -5x = 2 + 3 -5x = 2 + 3 Combine like terms: 2 + 3 = 5 -5x = 5 Divide each side by '-5'. x = -1 Simplifying x = -1
| -2x+41=2x+17 | | 3u+2=-19 | | 1/4-5/3 | | 9-6:-1/3-3 | | 3x^2-6x+5=2x(4-x) | | 3X+2x=4a | | -396/x-10=-22 | | graphy=90-x | | 9x-2(4-2x)=7x+16 | | y=90-x | | 4/7(56) | | 9x^3+35x^2+51x+36=0 | | 16x-21=12x-15 | | Y=12-2(5) | | 5/9/4/5 | | (5-3x)-(-4x+6)=(8x+11)-(-3x-6) | | 1000=0.1x+x | | 15(m-3)=90 | | Y=12-2(4) | | k+90=105 | | 6/7d-5=3/7d-2 | | 17+k=29 | | 1.6-4.8=-1.6 | | 2x+(2x+1)=8+(3x+3) | | 73/24=45/x | | 73/24=125/x | | 73/24=41/x | | 73/24=100/x | | 8x+56=104 | | 60x+20=40 | | 999/747 | | -12+8x=-4x+24 |